2015
DOI: 10.1186/s13643-015-0064-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of lower extremity amputation in the diabetic compared to the non-diabetic population: a systematic review protocol

Abstract: BackgroundDiabetic individuals have a largely increased risk of lower extremity amputation (LEA) compared with non-diabetic patients. Prior systematic reviews of incidence of LEA have some limitations with respect to lack of consensus in the definition of LEA, level of LEA (all, major, minor), and definition of source population (general population or population with diabetes at risk). The purpose of our review is to evaluate the incidence of LEA in the diabetic population and its differences with regard to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…As a consequence of DFUs, a lower limb is lost every 30 seconds somewhere in the world, and the probability of losing the other leg is 50% after 3 years. DFUs contribute to 85% of non-traumatic, lower-extremity amputations and lead to a 13%–17% mortality rate in patients with DM 4,5. In comparison to non-DFU patients, DFU patients have more days of hospitalization and more days requiring home health care, emergency department visits, and outpatient/physician office visits 6.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of DFUs, a lower limb is lost every 30 seconds somewhere in the world, and the probability of losing the other leg is 50% after 3 years. DFUs contribute to 85% of non-traumatic, lower-extremity amputations and lead to a 13%–17% mortality rate in patients with DM 4,5. In comparison to non-DFU patients, DFU patients have more days of hospitalization and more days requiring home health care, emergency department visits, and outpatient/physician office visits 6.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, depending on how the cases are defined and counted, the results can differ notably from study to study. According to a protocol of a systematic review by Kvitkina et al 21 on diabetes-related incidence rates, there are three methods for counting the number of LLA cases and therefore determining the numerator: 1) person-level: when only one amputation per person is counted; 2) case-level: when only one amputation per limb on the same admission is counted but amputations on different admissions are counted separately; and 3) procedurallevel: when all amputation procedures regardless of whether carried out at the same or different admissions are counted separately. In this study, we chose to report the data based on case level because it was compatible with the incidence studies that had clear methods.…”
Section: Lower Limb Amputation In Canadamentioning
confidence: 99%
“…Research has shown that the presence of foot lesions is a predictive mortality factor for the diabetic patient even at 10 years [19]. The diabetic foot generates 85% of amputations without a traumatic cause and corresponds to a mortality rate of 13-15% among diabetics [22]. The number of diabetic foot amputations has been steadily increasing and may be considered an indicator of the effectiveness of multidisciplinar y diabetic foot management.…”
Section: Resultsmentioning
confidence: 99%